Fitting a Sphere via Gröbner Basis - Lewis, R.; Paláncz, B.; Awange, Joseph (2018)
© 2018, Springer International Publishing AG, part of Springer Nature. In indoor and outdoor navigation, finding the local position of a sphere in mapping space employing a laser scanning technique with low-cost sensors is a very challenging and daunting task. In this contribution, we illustrate how Gröbner basis techniques can be used to solve polynomial equations arising when algebraic and geometric measures for the error are used. The effectiveness of the suggested method is demonstrated, thanks to standard CAS software like Mathematica, using numerical examples of the real world.